MARITAL CONFLICT RESOLUTION OF MIDDLE CLASS JAVANESE COUPLES - Andayani, Budi (Faculty of Psychology, Universitas Gadjah Mada, 2001)
This research set out to learn more about Javanese couple’s strategies in handling their conflict. The strategies of three couples from middle class social status, resident in the city of Yogyakarta, were explored by using semi-structured interview methods and repeating the interviews over three cycles. It was found that the strategies applied for managing conflict reflect avoidance of conflict, while the strategies for problem solving tend to be strategies related to self management, that is, the attempt to control oneself in order to cope with stress. It appears that these strategies are strongly influenced by traditional values and philosophies. Keywords: conflict- resolution; Javanese couples.